Algorithm for Identification Electromagnetic Parameters of an Induction Motor When Running on a Three-Phase Power Plant - D. S. Odnolko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Synthesized algorithm for electromagnetic rotor time constant, active resistance and equivalent leakage inductance of stator induction motor for free rotating rotor. The problem is solved for induction motor model in the stationary stator frame α-β. The algorithm is based on the use of recursive least squares method, which ensures high accuracy of the parameter estimates for the minimum time. The observer does not assume prior information about the technical data machine and individual parameters of its equivalent circuit. Results of simulation demonstrated how effective of the proposed method of identification. The flexible structure of the algorithm allows it to be used for preliminary identification of an induction motor, and in the process operative work induction motor in the frequency-controlled electric drive with vector control.